ANALISIS PENGARUH KELOMPOK ACUAN, PERSEPSI, DAN SIKAP TERHADAP KEPUTUSAN PEMBELIAN JASA KARTU SELULER IM3 - Nirwanto, Irfan Budi; Asakdiyah, Salamatun (Universitas Ahmad Dahlan, 2012)
In this study the authors chose the title â€œAn Analysis Of Category of Refference, Perseption, and Attitude Effect For Purchasing IM3 Celluler Service Decisionâ€ This research aims to find out how the influence of the reference group, the perception of and attitudes towards mobile card services purchasing decisions, either partially IM3 and simultaneous. Multiple linear regression analysis showed that the influence of the free variables of reference groups namely (X 1), perception (X 2), and (X 3) simultaneously bound variables that affect purchasing decisions (Y) is equal to 22.5% through the regression lines as follows: Y= 0,699-0, 019X1-0, 019X2 0, 778X3. The test results indicate that the variable t reference groups (X 1) and perception (X 2) partially do not affect significantly the purchasing decisions (Y) services of cellular card IM3. As for variable posture (X 3) partially affect significantly to purchasing decisions (Y) services of cellular card IM3. F test result obtained F-countdown of probability rate i.e. 9,293 0.000. Because the value of the probability of & lt; alpha 0.05, then it can be inferred that the references groups of variables (X 1), perception (X 2), and (X 3) a simultaneous effect on purchasing decisions (Y) services of cellular card IM3.